Situacion de la educacion agricola en Honduras - Avila, J.A.=700 1 Duarte, L.; Bonilla, I.; Romero, G.; Berrios Gomez, R.
(Es, En)
Ilus., 5 ref.
Keywords: EDUCACION AGRARIA; EDUCACION SECUNDARIA; HONDURAS